Etiologic, environmental and inherited risk factors in sarcomas. Issue 5 (21st October 2014) - Thomas, David M.; Ballinger, Mandy L.
Abstract : Sarcomas are a rare group of mesenchymal tumors affecting a younger population. The etiology remains unknown in most cases. Environmental factors that increase sarcoma risk include radiation exposure and chemical carcinogens. Several familial cancer syndromes confer sarcoma predisposition, such as the Li‐Fraumeni Syndrome (LFS). In this increasingly genomic focussed era of medicine, it will be clinically important to understand the genetic basis of sarcoma risk. J. Surg. Oncol. 2015 111:490–495 . © 2014 Wiley Periodicals, Inc.